Factors Affecting Systems Thinking Management: Educational Administration, Educational Organization and Educational Leadership - Ari Gunawan; Ali, Hapzi; Imron Rosadi, Kemas (International Journal of Advanced Multidisciplinary, 2023)
The Influence of Educational Administration, Educational Organization and Educational Leadership on Systems Thinking Management is a scientific article of literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of influence between variables that will be used in future research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. Research methods with risearch libraries are sourced from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) Educational Administration influences Management Thinking Systems; 2) Educational organizations influence Management Thinking Systems; and 3) Educational Leadership influences Systems Thinking Management.